Peran BMT Assyafiiyah dalam Pemberdayaan Perekonomian dan Kesejahteraan Desa (Studi Kasus Desa Kota Raman) - Azizah, Dwi Waliyatul Azizah; Ali, Ali Nur Yasin; Uyun, Qurotul Uyun; lia, Lia Febriyani (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
The economic recession that occurred in Indonesia caused the level of welfare to decline. One measure of welfare is by increasing the standard of living of the community. This study seeks to determine the role of small micro Islamic financial institutions or Baitul Maal wa Tamwil (BMT). BMT Assyafiiyah Bn Kcp Raman Utara is here as a solution for rural communities that have not been touched by banking institutions, is present as a solution to empowering the community's economy and increasing the welfare of the village community in Raman City with various financing offered. This research method uses descriptive research with a literature study approach. Previous research only focused on the development of MSMEs, therefore this research tries to look at the role of BMT in empowering the economy and welfare of villages. From this study found the role of BMT Assafiiyah BN Kcp Raman Utara in empowering the economy and welfare of the village of Kota Raman. Marked by the existence of financing such as mudharabah, murabahah and qardhul hasan financing, hawalah and ijarah and other financing. Social programs that use zakat, infaq, shadaqah funds for orphans, widows and CSR programs by providing assistance to the construction of mosques which really help the community's economy for their living needs and developing businesses that lead to falah.